The role of the Holy Spirit in Ghanaian Pentecostal churches: a missiological study - White, Peter; Niemandt, Cornelius Johannes Petrus (Nelus) (2014)
This article discussed the role of the Holy Spirit in Ghanaian Pentecostal churches from a missiological perspective. In order to achieve the aim for the topic, the article focused on one of the major factors that led to the rise and popularity of Pentecostalism in Ghana; i.e. the concern of the indigenes about their worldview not being addressed by the Western missionaries which came to serve in Ghana. The article argued that, in the desire for Ghanaians to have their worldview addressed, they resorted to Pentecostalism – a movement first introduced into Ghana by the African Initiated Churches. It is also argued that, though one of the factors that have made Pentecostalism to be accepted by Ghanaians is how it has addressed their worldview; Ghanaian Pentecostal Churches are of the view that the role of the Holy Spirit is the major factor for this increase.
Free